Radical difference : a defence of Hendrik Kraemer's theology of religions - Perry, Tim S., 1969- (Editions SR., 2006)
It is commonly assumed that all religions are essentially alike, that they are all common members of the genus Religion. But what if religions are not fundamentally similar after all? What if, on the contrary, it is better to presuppose a radical difference among the world's various religious communities, with each faith being defined by different beliefs, different practices, different world views, and different ways of life? Radical Difference: A Defence of Hendrik Kraemer's Theology of Religions explores the implications of this presupposition by examining the pioneering work of Dutch Reformed theologian and missionary Hendrik Kraemer. Perry shows that a critical reappropriation of Kraemer by contemporary Christian theology of religions can only help those Christians, especially evangelical Protestants, who find themselves equally unsatisfied with the various pluralisms and traditional responses, whether optimistic or skeptical, currently available. Increased global migration and technological advances have brought us closer together than ever before. At the same time, ethnic, cultural and religious tensions throughout the world have awakened us to issues of interreligious tolerance and cooperation. This book recognizes and addresses the impact differing religious beliefs, practices and world views have on our lives.